(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تراعى في إعداد الموازنة العامة للدولة عدة مبادئ، يتعلق بعضها بأصول تنظيم الموازنة العامة بشكل يكفل حق الشعب وممثليه بالاطلاع عليها، ومراقبة تنفيذها بصورة دقيقة وسهلة، ويتعلق بعضها الآخر بالمدة التي يجب أن تعد الموازنة من أجلها... ويسمح احترام هذه المبادئ بإعطاء السلطة التشريعية قدراً من الهيمنة على نشاط السلطة التنفيذية في المجال المالي، كما أنه يعكس الرغبة في إضفاء الدقة والوضوح على وثيقة الموازنة العامة لكي تكون المرآة الصادقة للوضع المالي للدولة. ومع تطور مفهوم الدولة ودورها والموازنة العامة، بدأت الكثير من الدول في التخلي عن الالتزام الدقيق بهذه المبادئ، ولم يكن هذا التخلي كلياً وإنما اقتصر في معظم الأحيان على تبني تطبيق أكثر مرونة للمبادئ المشار إليها.. وهكذا أصبح تطبيق هذه المبادئ والتقيد بها موضع اختلاف كبير بين علماء المالية العامة، فنقدها البعض ودافع عنها آخرون وقدم كل منهم حججه ومؤيداته. ومن أهم هذه المبادئ: مبدأ شمول الموازنة العامة، ومبدأ وحدة الموازنة العاملة، ... إلخ فمبدأ وحدة الموازنة، يهدف إلى إعداد وثيقة واحدة لموازنة الدولة، ويمثل الإطار الخارجي لها. أما مبدأ الشمول، فيهدف إلى ملأ هذا الإطار عن طريق التسجيل التفصيلي لكل تقدير لنفقة ولكل تقدير لإيراد دون إجراء مقاصة بين التقديرين، وبالتالي فهو يمثل المضمون الداخلي لمبدأ وحدة الموازنة. ونظراً إلى ارتباطهما الوثيق ببعض، وأهمية مراعاتهما، فضلاً عن التزام معظم الدول من حيث المبدأ بهما، اخترنا هذا الموضوع ليكون محوراً للبحث والمناقشة. هدفت الدراسة إلى التعريف بهذين المبدأين، وبيان العلاقة بينهما، ومبرراتهما، و النقد الموجه إليهما، والاستثناءات الواردة عليهما، وأخيراً استعراض الفروق الأساسية بينهما والنتائج المترتبة على ذلك وصولاً إلى نتائج البحث. Several principles are taken into account in the preparation of the general budget, some of them is to respect the organization of the general budget so as to ensure the right of the people and their representatives to be aware of it and monitor its implementation in an easy way, and also to respect the time duration, the general budget needs to be prepared. The respect for these principles allow giving the legislative authority a greater control of the executive authority activity in the finance field. It also reflects the desire to give the resolution and the clarity to the document of general budget in order to reflect clearly the financial situation of the state. With the development of the concept of the state, its role, and the general budget, many countries have begun to abandon the commitment to these principles. Actually, this was not to give up entirely but it was limited in most cases to adopt a more flexible application of the principles referred to. Thus, the implementation of these principles and the adherence to them has become the subject of a significant difference between the public finance scholars. Therefore , some bodies criticize it, and others defend it, and present their arguments. The most important principles are: the principle of inclusiveness and unity. The principle of unity aims at preparing one document for the state budget, and represent its external frame. The principle of inclusiveness aims at filling this frame through a detailed registry of each estimation of the expenses and revenues without the offset between them, and therefore, it represents the internal content of the principle of unity. We chose this topic because of the close link between them and the importance of observance, as well as most countries commit to them. The study aimed at defining these principles, their justifications, and discussing the link between them, criticism, the exceptions, as well as the fundamental differences between them, and the research results.